ANALISIS PENGUKURAN KUALITAS LAYANAN DENGAN PENDEKATAN SERVQUAL DAN TEORI ANTRIAN DI KANTOR POS - Cahyanti, Helda Mia (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
One way to survive in competition is having ability to give satisfied to the customer satisfaction principles. On the other hand, it should have measuring service quality with servqual approach. The destination of quality measuring is know about variable be included in variable position that must concentrate here, keep the good work, low priority, and possible overkill. The variables that go to concentrate here position, the factory must try more active to improve these variables in order that it can fill the customer desire. The variables belonging to this position is variable in comfortable about air conditioner, cleaner, friendly official, free parking place, accuracy delivery, and speed in service. From these variable belonging to concentrate here position, such as variable about accuracy delivery and variable about speed in service. Because of that, we must do measuring between coming and service time with queue theory. Besides, price minimize can decrease of queue with the way to establish the number of operator. With queue theory, it can increase operator become two peoples and total of excretion price become Rp21,477.7/hours with wait time in 0.3873144 hours/pack.